Anti-Müllerian hormone is an independent marker for oocyte survival after vitrification. Issue 1 (July 2020) - Melado, Laura; Arnanz, Ana; Bayram, Asina; Elkhatib, Ibrahim; De Munck, Neelke; Navarro, Alfredo Tomás; Coughlan, Carol; Lawrenz, Barbara; Fatemi, Human Mousavi
Highlights: Low serum AMH is correlated with lower survival rates after oocyte vitrification. Blastocyst formation is higher in fresh compared with warmed sibling oocytes. Abstract: Research question: This study explored the relationship between anti-Müllerian hormone (AMH) and oocyte survival after vitrification. The association between AMH and blastocyst formation after oocyte vitrification was also assessed. Design: A retrospective observational analysis was performed in a private IVF centre. A total of 4507 metaphase-II warmed oocytes were included from 450 couples, predominantly of Arab ethnicity. Between August 2015 and August 2018, couples underwent 484 intracytoplasmic sperm injection (ICSI) treatments using vitrified-warmed oocytes. Results: Patients' median age ± SD was 36.2 ± 6.1 years, AMH concentration 2.6 ± 3.4 ng/ml and body mass index (BMI) 26.5 ± 4.6 kg/m 2 . The oocyte survival rate after vitrification was 87.37 ± 20.42%. AMH concentration showed a significant correlation (Kendall's tau 0.087, P = 0.0079) with oocyte survival rate independent of oocyte yield. Correlation was significant (odds ratio 1.041, 95% confidence interval 1.007–1.077, P = 0.018) when a multivariant model was applied that included AMH, age and BMI. The receiver operating characteristic curve showed an AMH cut-off value of 1.09 ng/ml that could obtain at least a 70% survival rate, with an area under the curve of 0.669. Regarding embryo development in ICSI cycles including fresh and warmed oocytes for the same patient, blastocyst formation rate was higher in fresh compared with warmed oocytes ( P < 0.001). In this subgroup no significant correlation was seen between fertilization or blastocyst rate and AMH concentration. Conclusions: AMH concentration showed a significant correlation with oocyte survival. Blastocyst formation was significantly lower after oocyte vitrification, but no correlation was found with AMH. Clinicians should carefully evaluate oocyte vitrification for patients with AMH below 1.09 ng/ml and consider embryo accumulation for these patients in preference to oocyte accumulation.